Analisis Hasil Produksi Perikanan Budidaya Air Tawar di Kebumen Menggunakan Metode Clustering K-means - ikhsanuddin, rohmatulloh muhamad (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
Kebumen, as one of the districts in the south of Central Java Province with an area coverage of 26 sub-districts, has the potential for freshwater aquaculture production to reach 3,316,378 kg in 2022. This production can be optimized by creating clusters in sub-districts in Kebumen to utilize this area. Data mining using the k-means clustering method helps to group sub-district areas so that it can assist in decision making. Tests in data mining using Davies Bouldin with values k=2 to 10 show that the best value results, namely at value k=3, is 0.487. The K-means method with a value of k=3 produces 3 clusters with the result that cluster 1 consists of 19 sub-districts, namely the areas of Petanahan, Bulus Pesantren, Ambal, Mirit, Bonorowo, Prembun, Padureso, Alian, Poncowarno, Kebumen, Pejagoan, Sruweng, Rowokele, Sempor , Gombong, Karanganyar, Karanggayam, Sadang and Karangsambung. Cluster 2 consists of 1 sub-district, namely the Kuwarasan area, while cluster 3 consists of 6 sub-districts, namely the Ayah, Buayan, Puring, Klirong, Kutowinangun and Adimulyo areas.